Expanding Use of Telepractice in Speech-Language Pathology and Audiology. - Edwards, Marge; Stredler-Brown, Arlene; Houston, K. Todd (Volta Review)
Recent advances in videoconferencing technology have resulted in a substantial increase in the use of live videoconferencing--referred to here as telepractice--to diagnose and treat speech, language, and hearing disorders. There is growing support from professional organizations for use of this service delivery model, as videoconferencing technology can alleviate the effects of distance on access to care. As telepractice becomes a standard mode of conducting diagnostic and treatment services in speech, language, and hearing disorders, it is essential to assure that research supports its application in the field. Search criteria were established to identify publications, primarily in peer-reviewed journals, from 1995 to 2011. These studies generally validate the delivery of diagnostic and therapeutic services through telepractice when compared to traditional services delivered in a face-to-face clinical setting. Most studies examined adults and school-age children. The search was then expanded to identify diagnostic and treatment services for infants, toddlers, and young children. The existing literature compels professionals to conduct more research related specifically to the effectiveness and efficacy of telepractice.